Answer:
-315
Step-by-step explanation:
same terminal side
What do you need help with
The awnser would be-(4a+b-3) I hope this helps you
Answer:
Step-by-step explanation:
u799
Implicit expression refers to equation that are not strictly expressed in terms of y and x separately. In this case, the derivative of expression
<span>sqrt(xy)=x^2y+1 is
sqrt x * 0.5 y ^-0.5 dy + </span>sqrt y<span> * 0.5 x ^-0.5 dx= x^2 dy + 2xy dx
dy (x^2 - 0.5 (</span>x/y) ^0.5) = dx (2xy - 0.5 (y<span>/x)^0.5)
dy/dx = </span>(2xy - 0.5 (y/x)^0.5) / (x^2 - 0.5 (<span>x/y) ^0.5)</span>